2018
DOI: 10.1039/c7fo01898c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fisetin supplementation on inflammatory factors and matrix metalloproteinase enzymes in colorectal cancer patients

Abstract: A growing body of evidence indicates that inflammation is associated with tumorigenesis, metastasis and chemotherapeutic resistance in patients with colorectal cancer (CRC). Natural flavonoids are promising agents for inflammation-related tumor progression in patients with CRC. This study aimed to assess the efficacy of flavonoid fisetin supplementation on the inflammatory status and matrix metalloproteinase (MMP) levels in these patients. In this double-blind, randomized placebo-controlled clinical trial, 37 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 45 publications
2
43
0
Order By: Relevance
“…In the past few decades, medicines of herbal origin, including Rhizoma drynariae (75) and Baishao zongdai (68), demonstrated significant efficacy in terms of safety in the management of FM. Fisetin, a flavonoid polyphenol phytoconstituent, also showed promising potential for the clinical management of colorectal cancer (76). A few human clinical studies have been performed using fisetin as a dietary supplement for the management of various disorders, including frailty syndrome, mild cognitive impairment, diabetic nephropathy and Gulf War Syndrome (77).…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, medicines of herbal origin, including Rhizoma drynariae (75) and Baishao zongdai (68), demonstrated significant efficacy in terms of safety in the management of FM. Fisetin, a flavonoid polyphenol phytoconstituent, also showed promising potential for the clinical management of colorectal cancer (76). A few human clinical studies have been performed using fisetin as a dietary supplement for the management of various disorders, including frailty syndrome, mild cognitive impairment, diabetic nephropathy and Gulf War Syndrome (77).…”
Section: Discussionmentioning
confidence: 99%
“…To put this into context, the average daily consumption of Fisetin is thought to be 0.4 mg per day [ 109 ]. In terms of clinical trials, this 100 mg dose has been used in a colorectal cancer chemotherapy study and has been shown to reduce inflammatory markers, although numbers were small and no clinical cancer end points were assessed [ 121 ]. There were no safety issues at this dose and the research team felt there was potential for further studies to investigate its adjuvant value.…”
Section: Senotherapiesmentioning
confidence: 99%
“…Inflammation promotes carcinogenesis, metastasis and therapeutic resistance of colorectal cancer [ 119 , 120 , 121 ]. Therefore, a double-blinded, randomized placebo-controlled trial evaluated effects of supplementation with fisetin on inflammatory status and MMPs level in 37 CRC patients.…”
Section: Targeting Metastatic Cancermentioning
confidence: 99%
“…The fisetin supplementation, which began a week before chemotherapy and was continuous until the end of the second chemotherapy cycle, decreased plasma levels of IL-8, high sensitivity C-reactive protein (hs-CRP) as well as MMP-7 level. The efficacy of fisetin in the improvement of inflammatory status of colorectal carcinoma patients can be associated with its role of a complementary antitumor agent [ 119 ]. The effectiveness of chemotherapy in colorectal cancer patients evaluated as combined with the herbal agent MB-6 composed of fermented soybean extract, green tea extract, Antrodia camphorata mycelia, spirulina, grape seed extract, and curcumin extract.…”
Section: Targeting Metastatic Cancermentioning
confidence: 99%